Dominasi Ilokusi dan Perlokusi dalam Transaksi Jual Beli - Liya Umaroh; Neny Kurniawati (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2017)
‘The domination of Illocutionary and Perlocutionary in Buying and Selling Process’ was choosen as a title of this research. One of the biggest traditional market in Semarang, Pasar Johar was selected as a place to take the data because of its heterogeneity. Many buyers and sellers come from different cities, different ethnic groups, social strata, languages, dialects and diversity of cultural traditions that will produce complex utterance. Descriptive qualitative method was used in this research, which had purposes to provide in developing linguistic studies, especially in pragmatic speech acts. Result of the research shows tha ilocutionary and perlocutionary are dominant in the process of buying and selling.